Middle to Late Devensian glaciation of north‐east Scotland: implications for the north‐eastern quadrant of the last British–Irish ice sheet. (16th September 2016) - Merritt, Jon W.; Connell, E. Rodger; Hall, Adrian M.
ABSTRACT: We present a review of over 175 years of research into the Middle to Late Devensian (Weichselian) glaciation of NE Scotland based crucially on both its lithostratigraphic and geomorphic records. The location of the region, and surrounding seabed, makes this unusually detailed record significant for deciphering the former interactions and dynamics of Scottish and Scandinavian ice within the North Sea Basin (NSB), which continue to be controversial. A 12‐stage event stratigraphy is proposed based on a parsimonious interpretation of stratigraphic relationships, till lithology and regional clast fabrics, striae, subglacial bedforms, ice‐marginal features and published geochronometry at critical sites. The record of regional glaciation supports converging evidence that the north‐eastern quadrant of the last British and Irish Ice Sheet reached its maximum spatial extent in the late Middle to early Late Devensian and later re‐expanded following widespread internal glacial reorganizations, marine transgression and partial retreat from the central NSB. Retreat was interrupted by several glacial readvances of limited extent. Field‐captured data help to identify important events that are not clearly resolved from remote sensing alone, particularly regarding growth phases of the last glaciation.